HUBUNGAN KOMPONEN RUMAH DENGAN KEJADIAN TUBERKULOSIS DI DESA SAMURA KECAMATAN KABANJAHE KABUPATEN KARO TAHUN 2023 - Helfi Nolia Tambunan; Risnawati Tanjung; Erba Kalto Manik (Jurnal Ilmiah PANNMED (Pharmacist, Analyst, Nurse, Nutrition, Midwivery, Environment, Dentist), 2024)
the lungs, but it is not uncommon for these bacteria to attack other organs of the body such as bones, lymph nodes, kidneys and other organs. The aim of the research is to determine the relationship between ventilation, floor type, wall type, residential density and humidity with tuberculosis in Samura Village, Kabanjahe District, Karo Regency in 2023. Of the 125 data on tuberculosis cases in the working area of Kabanjahe community Health Center in 2022, Samura Village is the village that has the highest TB cases in Kabanjahe sub district, Karo Regency. This research was an analytic observational study using a case control study design that analyzes casual relationships by first determining the disease (outcome) and then identifying the causes (risk factors). The number of samples in this study was 23 case samples and 23 control samples. Data analysis carried out in this research was univariate analysis and bivariate analysis. The statistical test used is the chi-square test at a confidence level of 95% (?=0.05). The results of this study indicate that there was correlation between the physical condition of the house and the incidence of tuberculosis in the ventilation variable (p-value = 0.007), occupancy density variable (p-value = 0.037), and humidity variable (p-value = 0.039). While there is no relationship between the type of floor and the type of wall with the incidence of tuberculosis in Samura Village, Kabanjahe Sub District, Karo Regency. Multivariate analysis shows that ventilation makes the highest positive contribution to tuberculosis in Samura Village, Kabanjahe District, Karo Regency in 2023. The contribution of the positive beta coefficient (?) is 2.623 with Exp (?) namely 13.773. The results of this analysis show that air ventilation at home has a 14 times risk of contracting tuberculosis.